KAJIAN TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI KETIDAK-LANCARAN PENGEMBALIAN KREDIT USAHA KECIL (STUDI KASUS BANK MANDIRI PURWOKERTO) - Estiani, Tri Indah (www.bsi.ac.id, 2009)
Abstract:Small Business Credit nowadays is a priority program of the government in promoting economic activities in the State of Indonesia. Small business loans in the banking sector becomes very important for economic growth in the State of Indonesia. Supervision of smoothness or lack launch of small business credit banking becomes very important, especially because there are many small business loan repayment is not lancer. Therefore to know the cause of lack launch of Small Business Credit process, especially in terms of return on the Small Business LoanKeyword:Small Business Credit, Banking, Economic Growth